Design of a Guidance and Counseling Service Program in Assisting the Achievement of Adolescent Development Tasks in the New Normal Period (Study in Class VII of SMP Negeri 5 Kapur IX, Fifty Cities District) - Dita, Helendita; Suryadi, Suryadi (Holistic Science, 2022)
This research is motivated by the presence of students who are less independent in participating in the learning process, lack of interaction during the face-to-face learning process and there are still students who cannot accept the condition of the body. The purpose of this study was to describe the achievement of adolescent developmental tasks and to design a program of guidance and counseling services based on the results of problem identification. This research was conducted using a quantitative descriptive method. The sample of this study was 56 students in class VII taken using total sampling technique. The instrument used is the developmental task inventory (ITP).  The results of the research on the design of the Guidance and Counseling Service Program in Helping the Achievement of Adolescent Development Tasks in the New Normal Period (Studies in Class VII SMP Negeri 5 Kapur IX, Lima Puluh Kota Regency) seen from the achievement of adolescent developmental tasks in the new normal period are generally at the developmental level conformity with a score of 3.46 and the form of services and counseling provided, namely information services, group guidance services, collaboration services and bibliotherapy services for class VII SMP Negeri 5 Kapur IX, Lima Puluh Kota Regency which has not achieved the developmental tasks that should..